Lemmeguide / Muhammad Fikri H.R … [et al.] - H.R, Muhammad Fikri; N, Nor Haziq Ezmi; Z, Muhammad Luqman; M.Z, Fatin Aza Shamiemy; M.F, Nurulain Husna; Z, Khadijah; A.W, Mohd Zafri (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
This project addresses the significant challenge faced by blind individuals in safely and independently navigating their surroundings. Traditional blind sticks offer limited assistance, resulting in blind travellers relying on external guides or aids like sighted assistance or trained animals. To reduce this reliance, our aim is to develop a novel assistive device integrating a camera and LIDAR sensor to detect obstacles and stairs in the blind person's path. This innovative product seeks to enhance spatial awareness and enable autonomous navigation for the user. Leveraging advanced technology, the device delivers real-time feedback through haptic signals, empowering visually impaired individuals to navigate with increased confidence and independence while using the device. This device holds promise as a potential cornerstone in the daily lives of blind individuals.